Graphic Organizers to Improve Students’ Writing on Recount Paragraphs - Mega Mulianing Maharani (Metathesis: Journal of English Language, Literature, and Teaching, 2018)
Writing is said to be difficult for the undergraduate students of second semester students of English department of UNISSULA. They found many difficulties in some aspects such as topic sentence, supporting sentence and concluding sentence. There were 10 of 23 students who got 75 on their writing score. Hence, the writer wanted to help them in improving their writing quality especially on those main structure of a paragraph by applying graphic organizers. Graphic organizers were used in the teaching learning process by conducting action research. The action research used two cylces. The results were that the students’ writing is better. The way they wrote topic sentence, supporting sentence, and concluding sentence were better than the previous one in the preliminary cycle. It was proved by the percentage of the students who got the score under the standard score of writing, namely, 75.